An analysis of the Inventory Level of Consumables in the Wards of a Tertiary Care Teaching Hospital in South India - Bhargav Kumar, Rajesh Kamath2 , Jibu Thomas3 , Karan Giriyan4, Nagraj5 , Abhishek Pallerla6 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Material management is important and crucial for all healthcare industries because it not only deals with thefinancial aspects but also deals with the well-being of the hospital and quality care of the patient. Reducinginventory cost is a critical responsibility of healthcare managers in hospitals. Inventory management shouldbe done with the help of proper value analysis. This study attempts to assess the inventory techniques andmonthly maintenance figure which have contributed to efficient inventory management in a tertiary careteaching hospital